Efektivitas Model Project Based Learning Terintegrasi Google Earth Terhadap Berpikir Kritis IPAS di SD - Ahsani Taqwim; Hisny Fajrussalam; Nenden Permas Hikmatunissa (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to evaluate the effect of project-based learning supported by Google Earth in improving critical thinking skills in science lessons for elementary school level. The low level of critical thinking skills among elementary school students in the science curriculum is a major factor in this study, especially related to the issue of environmental change; therefore, it is necessary to implement teaching methods that encourage students to be more active, critical, and involved in the learning process. The methodology used in this study is a quantitative approach with an experimental design involving heterogeneous groups. The research sample consisted of 42 students randomly selected from the experimental group and the control group. Data analysis was carried out using a pre-test and post-test on critical thinking skills. The results of the data analysis were assessed through correlation tests, homogeneity tests, independent t-tests, and N-Gain tests. The results showed that the average post-test score for the experimental group reached 80.24, which was higher than that of the control group. The N-gain value of the experimental group reached 65.60%, which is considered good, while the R-squared value of 0.648 indicates an effect on critical thinking skills. Therefore, project-based learning strategies supported by Google Earth have proven effective in improving students' critical thinking skills in science education at the elementary school level.